The impact of exposure on second language acquisition - Jahrani, Ahmad (Universitas Sarjanawiyata Tamansiswa, 2024)
Exposure to English is something that learners experience in their daily lives. When they are doing their everyday activities, they will encounter English words. When they watch television, listen to a song, play games, or scroll through social media, they are exposed to English and this exposure can affect their second language acquisition. This research aimed to describe the impact of exposure on second language acquisition. The method used is the Literature review method. With this research, it is expected to find the impact of exposure on second language acquisition. The data shows that that exposure has a positive impact on second language acquisition. Language exposure is essential for learning and mastering a second language. Learners who have had a lot of exposure to the language have a better chance of speaking and understanding it. In conclusion, the majority of the articles examined agree that exposure helps people learn a second language.